Brief Notes on Friedrich A. von Hayek’s Epistemology - Nogueira, Jorge Henrique de Saules (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2016)
Hayek’s epistemological approach points to fallibility, ignorance and knowledge fragmentation in society. His epistemology is structured in order to reveal the impossibility of creating desirable social orders from a deliberate human will aimed at that purpose. The understanding of Hayek’s epistemology contributes to the discussion about crystallized dogmas in the humanities and social sciences, serving as a powerful counterpoint to the predominant thought in the political, legal and academic Brazilian scenario.